Understanding the Design of Research and Development Methods in the Field of Education - Afriani, Linda; Mutmainnah; Sunarni (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
Research and Development (R&D) plays a crucial role in modern education to create innovative and effective learning products and solutions. This article discusses the R&D method in education, covering the stages from needs analysis, prototype development, validation testing, to large-scale implementation. This research uses a literature review method to gather information from various credible sources. The results show that the R&D method, with a structured and iterative approach, is capable of producing relevant and adaptive educational products, thus improving the quality of learning and supporting student and teacher engagement. However, challenges such as limited resources and understanding of research design are obstacles that need to be overcome. In conclusion, R&D offers a strong foundation for continuous and evidence-based educational innovation.